Pemasangan Convex Mirror di Blind Spot Dusun Tidaran 1 Desa Candiretno dalam Rangka Mitigasi Risiko Kecelakaan - Muhammad Aldo Savero; Aldias Gendis Syandiva; Selvi Septiana Putri; Dhikaz Wening Wulan; Herlina Eka Ramadani; Irma Agustin; Bagas Safrudin; Wildan Dzaki Mukholadun; Shuluh Aziki; Rizky Rizky; Ad’wa Fauzan; Niken Aulia Putri; Sri Sarwanti (Lembaga Pengembangan Kinerja Dosen, 2025)
Tidaran 1 Hamlet, Candiretno Village, Magelang Regency, is a rural area with quite heavy traffic in several areas. One location of particular concern is the bends and T-junctions in RT 11, which are frequently used by both two-wheeled and four-wheeled vehicles. This area is known to be an accident-prone area due to blind spots that obstruct the view of drivers from both directions. Unfortunately, to date, there are no safety facilities such as traffic signs or convex mirrors to aid visibility. Seeing this problem, students participating in the Community Service Program (KKN) from Tidar University conducted an intervention based on community needs. One effort was the installation of convex mirrors to minimize the risk of accidents. This activity was carried out using an action research method (action research), which included field observation, risk analysis, solution design, implementation, and impact evaluation. Throughout the process, students actively involved the community, the RT head, and village officials to ensure the proposed solution was participatory and sustainable. Convex mirrors with a diameter of 80 cm and a 2.5-meter-high support pole were installed at strategic points on the bends. Following the installation, follow-up observations and interviews with local residents were conducted. The results showed a significant improvement in visibility for drivers, especially at night and in similar weather. Residents reported feeling safer, less hesitant when crossing, and more alert to oncoming traffic. This program not only improved safety but also raised public awareness of the importance of traffic management. Therefore, similar interventions can be replicated in other vulnerable areas, with collaborative support from the community, universities, and village government.